2017
DOI: 10.1371/journal.pone.0190310
|View full text |Cite
|
Sign up to set email alerts
|

Independent relationship between serum ferritin levels and dyslipidemia in Chinese adults: A population study

Abstract: ObjectiveSeveral studies have indicated that elevated levels of circulating ferritin are associated with disturbances in energy metabolism. But none of this gave a clearly pathologic mechanism. We aimed to explore the independent relationship between serum ferritin levels and dyslipidemia.MethodsWe performed multivariable logistic regression analyses to estimate the odds ratios (ORs) for dyslipidemia, lipid parameters, the homeostasis model assessment of insulin resistance (HOMA-IR) and the risk of diabetes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 32 publications
5
35
1
Order By: Relevance
“…However, according to Mullis et al ( 2012 ), the infectivity of Betacoronavirus 1 on the surface of romaine lettuce under household refrigeration conditions extended to 14 days. Fomite transmission of viral respiratory diseases, including coronaviruses and less persistent viruses, has been previously proven or suspected (Boone and Gerba 2007 ; Xiao et al 2017 ). Those findings support the possibility of COVID-19 spread through food and food packaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Mullis et al ( 2012 ), the infectivity of Betacoronavirus 1 on the surface of romaine lettuce under household refrigeration conditions extended to 14 days. Fomite transmission of viral respiratory diseases, including coronaviruses and less persistent viruses, has been previously proven or suspected (Boone and Gerba 2007 ; Xiao et al 2017 ). Those findings support the possibility of COVID-19 spread through food and food packaging.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Jehn et al showed that SF was positively correlated with elevated TG in 6044 American adults [46]. Recently, Li et al showed SF values were significantly associated with TC, LDL-C, TG, and HDL-C independent of diabetes or IR in a Chinese population in both genders [47]. However, Yoo et al showed that significant associations of high SF with TG and HDL-C in young non-obese adults only existed in women [48].…”
Section: Discussionmentioning
confidence: 99%
“…Serum ferritin and plasma copper have been associated with an improved blood lipid profile, corresponding to a reduced risk of hyperlipidemia [ 12 , 13 ]. However, conflicting associative patterns have also been reported [ 14 ]. Since most existing studies were observational and often complicated by reverse causality and residual confounding, it is still unknown whether these associations indicate causal relationships.…”
Section: Introductionmentioning
confidence: 99%